2021
DOI: 10.1177/0333102420983292
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of erenumab, galcanezumab and fremanezumab in pregnancy and lactation: Analysis of the WHO pharmacovigilance database

Abstract: Objective To assess the safety profile of erenumab, galcanezumab and fremanezumab in pregnancy and lactation. Methods Safety reports of suspected adverse drug reactions were retrieved from VigiBase as of 31 December 2019, for a case-by-case assessment and disproportionality analysis using the reporting odds ratio (ROR). Results There were 94 safety reports: 50 (53.2%) on erenumab, 31 (33.0%) on galcanezumab, and 13 (13.8%) on fremanezumab. In five (5.3%) safety reports, drug exposure occurred prior to pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 32 publications
1
51
0
4
Order By: Relevance
“…However, these studies require a system to collect pregnant women and a sufficient number of cases to be conducted. Given the possibility that safety information for pregnant women can be obtained earlier by using spontaneous reports, some reports using the spontaneous reporting database have been reported [2][3][4][5][6]. Lareb, a pharmacovigilance center in the Netherlands, is also developing a toolkit for monitoring drug safety in pregnant women under the guidance of the World Health Organization, in which the use of a spontaneous reporting database is discussed [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies require a system to collect pregnant women and a sufficient number of cases to be conducted. Given the possibility that safety information for pregnant women can be obtained earlier by using spontaneous reports, some reports using the spontaneous reporting database have been reported [2][3][4][5][6]. Lareb, a pharmacovigilance center in the Netherlands, is also developing a toolkit for monitoring drug safety in pregnant women under the guidance of the World Health Organization, in which the use of a spontaneous reporting database is discussed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most malformations occur prior to the eighth week after conception because of an abnormal developmental process (3). Renal aplasia, which was reported in association with fremanezumab in one safety report included in our study (4), indicates that kidneys undergo no primary growth or development, and differs from renal agenesis whereby kidneys are absent because the first steps of development do not occur (5). Current literature suggests that the risk of birth defects from NSAIDs and aspirin use in the first trimester cannot be excluded but appears low based on conflicting findings affected by the inherent limitations of observational studies and small sample sizes (6,7).…”
mentioning
confidence: 57%
“…Therefore, after this period, due to poor transfer and low oral bioavailability, anti‐CGRP antibodies are unlikely to cause adverse effects in a full‐term healthy child. No safety issues have emerged for galcanzumab in lactation so far [57]. If clinically needed, galcanezumab could be considered in breastfeeding women after the first postpartum week.…”
Section: Cluster Headachementioning
confidence: 99%
“…Animal studies have not reported adverse reproductive toxic effects [56]. Human immunoglobulin (IgG) is known to cross the placental barrier, but no specific safety issues have so far emerged with use of anti‐GCRP antibodies in pregnancy [57]. As real‐life data are still limited, it is preferable to avoid the use of galcanezumab during pregnancy as a precautionary measure.…”
Section: Cluster Headachementioning
confidence: 99%